Characterization of tamarind biomass to substantiate the feasibility towards alternative fuel. (March 2023) - Amulani, Amit; Nandanwar, Tanmay; Baskaran, K.; Prakash, R.; Mohan, C.G.
Highlights: To assess the feasibility of producing biofuel from Tamarind biomass. Thermal and physical characterization of Tamarind biomass samples were carried out. Tamarind nut powder has great potential for the production of pyrolytic oil. The physio chemical properties of bio oil obtained were studied. Bio oil produced from pyrolysis of Tamarind seed can be substituted for fossil fuels. Abstract: Sustainable energy resources development from every possible route is the utmost priority in today's modern scenario around the globe. This situation reaches highly alarming rate after the pandemic situation due to the shortcomings on ease transportation viability among all the countries. Therefore, the present work aims at developing a sustainable biofuel from Tamarind seed biomass samples and to evaluate its suitability for various power generation applications. The proposed work consists of three samples: tamarind shell (TAN1), tamarind nut with peel (TAN2) and tamarind nut without peel (TAN3) undergoing physicochemical and thermal analyses to analyse their feasibility as a biofuel. Fourier transform infrared spectroscopy (FTIR) concluded high oxygenated compounds mainly alcohols, esters and carboxylic acids were determined at higher wave numbers. Ultimate and proximate analyses gave high amounts of carbon, volatile matter and low nitrogen and ash content. Thermogravimetric (TG) analyses showed the maximum mass loss in the temperature range of 150 °C–400 °C and confirm the presence of volatile compounds. It was mainly due to the degradation of hemicellulose. Calorimetry test gave high heating value (HHV) results and those compared with the empirical values calculated using the ultimate analysis equation. TAN3 is selected as a promising feedstock for pyrolysis and the characterization results signify the presence of organic compounds and infer high energetic value and bio refining potential. The bio oil obtained was characterized and analysed using GC–MS, FTIR, and H NMR to assess the bio oil potential as alternative fuel and presented in this paper.